Investigation the Effect of the Application of Single and Mixing of Propyzamide and Ethofumesate Herbicides in the Control of Dodder (Cuscuta Campestris), Grass and Broad Leaves Weeds of Sugar beet (Beta vulgaris L.) - Sayyed Mahdi Hosseyni; Hossein Najafi; Behzad Sani; Hamid Mozafari (Ikufīziyuluzhī-i Giyāhān-i Zirā̒ī)
In order to investigation the effect of the application of single and mixing of propyzamide and ethofumesate herbicides in the control of dodder, grass and broad leaves weeds of sugar beet, three experiment carried out at the greenhouse of sugar beet seed breeding research institute in 2017. The experiments were performed in a completely randomized design with 30, 10 and 9 treatments and four replications, respectively. Result showed that the effect of mixing different doses of Propyzamide and Ethofumesate herbicides and species of different area dodder on all studied traits in the present study was significant 1%. In general, the percentage of final germination (82.7%), daily germination rate (0.18 days) and the percentage of connection of Ardabil dodder to the host plan (82.7%) were higher than Alborz and Qom species. The highest percentage of weed conection of the dodder to the sugar beet was observed in the treat that cultivation distance of 5 cm. Application of Propisamide 2.5 L.ha-1 and Propisamide 1.5 L.ha-1 + Ethofumesate 1 L.ha-1 in connecting the dodder to the host, compared to Ethofumesate could control of dodder weeds (100%) and reduction of fresh and dry weights, density and chlorophyll of thin and broad leaveas weed and increased leaf chlorophyll and yield of sugar beet in green house condition. Therefore, the application of these treatments can be used in the control of parasitic, thin and broad leaves weed of sugar beet and application Propisamide 1.5 L.ha-1 + Ethofumesate 1 L.ha-1 in connecting the dodder to the host, can be considered in addition to the mentioned effects and in reducing the environmental effects of the use of chemical herbicides.